A note on integral transforms and differential equations - Kilicman, Adem; Eltayeb, Hassan; Ismail, Mat Rofa (Institute for Mathematical Research, Universiti Putra Malaysia, 2012)
In this work a new integral transform, namely Sumudu transform was applied to solve linear ordinary differential equations with constant coefficients with convolution terms. Further in order to generate a pde with non constant coefficients, the convolutions were used and solutions were demonstrated.